PENERAPAN METODE PEMBELAJARAN INQUIRY DALAM PENINGKATAN RASA INGIN TAHU DAN KREATIVITAS SISWA PADA MATERI KALOR DI SMA NEGERI 3 PADANGSIDIMPUAN - Nur Aisyah Harahap (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2018)
One of the demands of the Curriculum for teachers in learning, using the learning models appropriate to the characteristics of the material and their students. But the reality on the ground shows teachers generally use methods lectures are teacher centered and less teachers facilitate students to work in groups in learning. One form of the model that can enable students work together in learning is modelInquiry. The purpose of this study was to describe the competence of physics students. This type of research is research action class. The location of the research of SMA Negeri 3 Padangsidimpuan. The subject of research grade X with a total of 29 students. The research was conducted by two cycle consists of four steps of research, namely planning, implementation, observation and reflection. Research instrument consisting of a sheet of observation and tests the student's competence. Technique of data analysis was descriptive. Implementation research is held in even-numbered Annual semester Teaching 2013/2014. The results showed an increase in the competence of physics students. The results of the three cycles undertaken showed an increase in the percentage of students who achieve a minimum criterion. The percentage of students who complete learning increased from 36% in cycle I became the 88% in cycle III. The average value of student learning outcomes have also been increased from 66.88 on cycle I became 85.52 cycle III. Thus, it can be concluded the implementation model of inquiry can improve the competence of physics students of class X SMA Negeri 3 Padangsidimpuan.